A dual-band bandpass filter using integrated stepped impedance resonators. Issue 1 (2nd January 2016) - Pal, Manimala; Sarkar, Biswajit; Sarkar, Pankaj; Ghatak, Rowdra
Abstract : In this article, a compact dual-band bandpass filter (BPF) using integrated stepped impedance resonators (SIRs) is presented. The proposed filter topology consists of an outer open stub–loaded SIR to achieve lower passband of 2.45 GHz. The inner inter-coupled SIRs contribute to the 3.5 GHz band. The passband selectivity is achieved by introducing spur line in the input–output feed line sections that create a transmission zero at 2.2 GHz. A hook-shaped open stub is also added to bring about transmission zero at 4.55 GHz. The overall layout makes the filter compact with a size of 0.21 λg × 0.19 λg at 2.45 GHz. The insertion loss is within 1.75 dB for both the passbands. A prototype is developed with measured results in close agreement with the simulated results.